Ghrelin and Cannabinoid Functional Interactions Mediated by Ghrelin/CB1 Receptor Heteromers That Are Upregulated in the Striatum From Offspring of Mice Under a High-Fat Diet - Lillo, Alejandro; Lillo, Jaume; Raïch, Iu; Miralpeix, Cristina; Dosrius, Francesc; Franco, Rafael; Navarro, Gemma (Frontiers in Cellular Neuroscience, 2021)
There is evidence of ghrelinergic-cannabinoidergic interactions in the central nervous system (CNS) that may impact on the plasticity of reward circuits. The aim of this article was to look for molecular and/or functional interactions between cannabinoid CB1 and ghrelin GHS-R1a receptors. In an heterologous system and using the bioluminescence resonance energy transfer technique we show that human versions of cannabinoid CB1 and ghrelin GHS-R1a receptors may form macromolecular complexes. Such receptor heteromers have particular properties in terms of CB1/Gi-mediated signaling and in terms of GHS-R1a-Gq-mediated signaling. On the one hand, just co-expression of CB1R and GHS-R1a led to impairment of cannabinoid signaling. On the other hand, cannabinoids led to an increase in ghrelin-derived calcium mobilization that was stronger at low concentrations of the CB1 receptor agonist, arachidonyl-2'-chloroethylamide (ACEA). The expression of CB1-GHS-R1a receptor complexes in striatal neurons was confirmed by in situ proximity ligation imaging assays. Upregulation of CB1-GHS-R1a- receptor complexes was found in striatal neurons from siblings of pregnant female mice on a high-fat diet. Surprisingly, the expression was upregulated after treatment of neurons with ghrelin (200 nM) or with ACEA (100 nM). These results help to better understand the complexities underlying the functional interactions of neuromodulators in the reward areas of the brain.